Hubungan Pola Asuh Orang Tua Dan Stress Level Dengan Mekanisme Koping Pada Remaja Usia Pertengahan Di SMA Parulian 1 Medan - Siburian, Intan Teresya; Tambunan, Dior Manta (Indonesian Trust Nursing Journal, 2024)
The level of stress experienced by some students, parenting is very valuable or important. Parenting is the relationship between children and parents during parenting activities. Coping strategy is a way to solve or change the situation in solving the problem at hand. The objective of this study is to determine the relationship between parenting patterns and stress levels with coping mechanisms in mid-age adolescents at Senior High School Parulian 1 Medan. This type of research is quantitative with cross sectional design. The sampling technique used purposive sampling as many as 115 respondents. Data analysis using Chi Square test. The results of this study indicate that there is a significant relationship between stress levels and coping mechanisms with a p-value of 0.001 and there is no relationship between parenting patterns and coping mechanism with a p-value of 0.775 in middle age adolescents at Senior High School Parulian 1 Medan. There is a significant relationship between stress level with coping mechanisms. This shows that the better the coping mechanisms coping mechanisms used, the lighter the level of stress experienced and the researcher argues that parenting is not related to coping mechanisms. Researchers argue that parenting does not relate to coping mechanisms because there are several other factors that influence because there are several other influencing factors such aspersonality type, family personality, family communication, juvenile delinquency, self-concept and other factors one's environment.